Informal Gold Miners, State Fragmentation, and Resource Governance in Bolivia and Peru. (May 2022) - Toledo Orozco, Zaraí
ABSTRACT: High commodity prices have led to the proliferation of informal gold mining in the Andes. Despite their limited financial capacity, informal gold miners have proved capable of influencing national-level policy outcomes. Why are they able to do so? This study puts forward a comparative study of Bolivia, where informal miners have been politically incorporated, and Peru, where they have been traditionally excluded. It shows how, despite the very different institutional contexts, informal miners are similarly capable of leveraging their contribution to the local economy and the fracture between the central state and its peripheral branches to form pressure groups with local authorities. Based on 120 interviews with politicians and leaders from the largest gold-mining communities in Bolivia and Peru, this study contributes to the scholarship on state-society relations, resource politics, and decentralization by outlining the conditions and mechanism through which informal groups contest exclusionary resource governance in fragmented states.